Hukum Islam antara Positivisme dan Idealisme - Mashadi; Muannif Ridwan (Indra Institute Research & Publication, 2022)
This article discusses the relationship between Islamic law and positivism which has a very close relationship with one another. Islamic law is a law that is based on and sourced from the Qur'an as a revelation sent down by Allah to the Messenger of Allah to be given to his people as a way of life for the Muslim community and in the Qur'an itself there are rules, commands and prohibitions. that must be carried out by Muslims around the world in order to get a reward and enter the paradise of Allah SWT. In Islamic law itself there is reasoning and analysis which is very concrete evidence in terms of human delays in exploring science and law that live and develop in society. While the law of positivism is a worldly interest that is related to outward and material interests with its various intricacies, this law is man-made in which there are also prohibitions and orders that regulate mankind in the form of a nation and state. Islamic law is a law established by Allah to improve the benefit and welfare of Muslims in the world, both physically and mentally, in this world and the hereafter.Positivism and idealism in Islamic law have a very good and harmonious relationship with each otherasfound in Surah Al-SYams verse 7-10 which has the following meaning: